Peter Voulkos : the breakthrough years. (London : Black Dog, 2016)
Peter Voulkos: The Breakthrough Years' is the first monograph in over 20 years on the artist Peter Voulkos. Covering the most prolific span of Voulkos career, from the early 1950s to the 1970s, this book includes both his well-known ceramic works as well as his largely overlooked paintings. While Voulkos work has most often been discussed in relation to the practice of ceramics, the writers in this book explore the artist s work through the scope of art history and in a contemporary light. In addition to engaging with the breakthrough years of Voulkos practice, a focus is also put on his legacy today, as numerous artists explore the expressive language of clay that he helped to re-invent. The book includes texts from writers Andrew Perchuk, Deputy Director at The Getty Research Institute; and Jenni Sorkin, Assistant Professor in Contemporary Art at UC Santa Barbara.
Voulkos: The Breakthrough Years, Museum of Arts and Design, New York, October 18, 2016 to March 15, 2017 and at Renwick Gallery in Washington from April 17 to August 20, 2017
boek
Keywords: Voulkos, Peter